Pemecahan Masalah Matematis Siswa Kelas VIII Menggunakan PMRI melalui LSLC pada Materi Gradien - Rio Kurniawan; Ratu Ilma Indra Putri; Sunaryati Sunaryati (Universitas Hamzanwadi, 2020)
This study aims to discover how the mathematical problem-solving ability of students in class VIII using Pendidikan Matematika Realistic Indonesia (PMRI) through Lesson Study for Learning Community (LSLC) on straight-line gradient material. The subjects of this Study were Students of class VIII.B Srijaya State Junior High, totaling 32 students. The learning process takes place adapted to the principles and characteristics of PMRI through the LSLC system. Data collection the techniques used in this study were observation, written tests consisting of two problem descriptions, and interviews conducted to obtain supporting data. The observation was to see student activities during the learning process. The tests are conducted to find out how students mathematical problem-solving abilities. The interview is used to confirm the student's answers. Obtained students' mathematical problem-solving abilities on the Straight-Line Gradient subject and had reached the indicators of understanding the problem, planning solutions, and implementing plans with the most indicators often appear is the indicator of planning a solution. In contrast, the indicator that rarely appears is the indicator of the truth of the completion of the problem. The conclusion of this research is mathematical problem solving of 8th-grade students using PMRI through LSLC on gradient material category was enough.